Strategi optimalisasi pemasaran digital guna menaikkan omzet penjualan Ayam Geprek Bonresva Unipessoal, Lda di platform e-commerce. - Abilio Correia da Cruz; Leonildo Freitas dos santos Sequeira (Advances In Education Journal, 2025)
By utilizing digital marketing, businesses are expected to gradually increase their sales.Ayam Geprek Bonresva Unipessoal-Lda, established in 2021 and owned by Bonifacio Soares da Silva, is a small and medium-sized enterprise (SME) that has grown and expanded its operations. Located in a strategic location on Jl. Delta 3 Dili, Timor-Leste, this eatery offers delicious Ayam Geprek with complete toppings, cheese, and tofu at affordable prices. In the digital age, Bonifacio Soares da Silva, as the owner of Ayam Geprek Bonresva Unipessoal-Lda, has wisely recognized the potential of online marketing as the key to the success of his business. With daily revenue of 3 million rupiah through offline channels, the next strategic step is to expand their presence in the digital realm. Marketing through social media platforms, particularly Facebook and TikTok Instagram, and the use of banners as a strategy to attract customers, are considered strategic moves that will enable them to reach more potential customers. The selection of Ayam Geprek Bonresva Unipessoal-Lda as the focus of this research is highly appropriate due to its strategic location, right on the roadside, making it a top choice for many passersby